Occupational violence toward mental health professionals during the COVID-19 pandemic: an international study - Robles, Rebeca; Kogan, Cary S.; Medina-Mora, María Elena; García-Pacheco, José Ángel; Rebello, Tahilia J.; Khoury, Brigitte; Kulygina, Maya; Reed, Geoffrey M. (Frontiers in Psychiatry, 2025)
IntroductionAccording to pre-COVID-19 pandemic studies, occupational violence (OV) toward mental healthcare professionals (MHCPs) is a common phenomenon with important consequences for their own mental health. This study sought to assess the prevalence of different types and sources of OV toward MHCPs during the COVID-19 pandemic, analyze the risk for OV conferred by relevant factors, and compare the emotional distress reported by MHCPs with and without OV.MethodsThe study is an international cross-sectional Internet-based study completed by 3,325 MHCPs having provided direct clinical services during the COVID-19 pandemic.Results13.11% experienced OV. The most frequent type/source of OV was psychological violence inside the workplace (59.6% of those who reported OV). Risk factors for any type/source of OV being younger, working in emergency services, treating COVID-19 patients, and living in a lower to upper middle-income country. Emotional distress was higher in those who had experienced OV. Risk factors for emotional distress among those reporting OV included being younger and having experienced physical violence outside the workplace.DiscussionApproximately one in ten MHCP experienced OV during the COVID-19 pandemic. This figure is consistent with the range of OV against MHCPs reported prior to the pandemic and indicates that efforts are needed to prevent and manage OV and its negative emotional consequences among MHCP, particularly in aforementioned high-risk groups during health emergencies, and addressing both proximal and distal environmental factors related to OV toward MHCPs.